Back2Action: effectiveness of physiotherapy blended with eHealth consisting of pain education and behavioural activation versus physiotherapy alone—protocol for a pragmatic randomised clinical trial for people with subacute or persistent spinal pain. Issue 1 (7th January 2022) - Bijker, Lisette; de Wit, Leonore; Cuijpers, Pim; Poolman, Eva; Scholten-Peeters, Gwendolijne; Coppieters, Michel W
Abstract : Introduction: Psychosocial factors predict recovery in patients with spinal pain. Several of these factors are modifiable, such as depression and anxiety. However, primary care physiotherapists who typically manage these patients indicate that they do not feel sufficiently competent and equipped to address these factors optimally. We developed an eHealth intervention with a focus on pain education and behavioural activation to support physiotherapists in managing psychosocial factors in patients with spinal pain. This paper describes the protocol for a pragmatic randomised clinical trial, which evaluates the effectiveness of this eHealth intervention blended with physiotherapy compared with physiotherapy alone. Methods and analysis: Participants with non-specific low back pain and/or neck pain for at least 6 weeks who also have psychosocial risk factors associated with the development or maintenance of persistent pain will be recruited in a pragmatic multicentre cluster randomised clinical trial. The experimental intervention consists of physiotherapy blended with six online modules of pain education and behavioural activation. The control intervention consists of usual care physiotherapy. The primary outcomes are disability (Oswestry Disability Index for low back pain and Neck Disability Index for neck pain) and perceived effect (Global Perceived Effect). Outcomes will be assessed at baseline and at 2, 6 and 12 months after baseline. The results will be analysed using linear mixed models. Ethics and dissemination: The study is approved by the Medical Ethical Committee of VU Medical Center Amsterdam, The Netherlands (2017.286). Results will be reported in peer-reviewed journals, at national and international conferences, and in diverse media to share the findings with patients, clinicians and the public. Trial registration number: NL 5941; The Netherlands Trial Register.